2016
DOI: 10.1155/2016/6106029
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics ofH. pyloriand Non-PyloriHelicobacterSpecies to Identify New Regions Associated with Its Pathogenicity and Adaptability

Abstract: The genus Helicobacter is a group of Gram-negative, helical-shaped pathogens consisting of at least 36 bacterial species. Helicobacter pylori (H. pylori), infecting more than 50% of the human population, is considered as the major cause of gastritis, peptic ulcer, and gastric cancer. However, the genetic underpinnings of H. pylori that are responsible for its large scale epidemic and gastrointestinal environment adaption within human beings remain unclear. Core-pan genome analysis was performed among 75 repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 84 publications
1
19
0
Order By: Relevance
“…In order to adapt to a variety of environments, bacteria have to change their genomes, but living in monotone habitats would have smaller pangenome [76]. Most of the Neisseria species colonize on the mucosa, which may be the reason that the pangenome size is relatively small compared with other niche diversity species [77, 78].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to adapt to a variety of environments, bacteria have to change their genomes, but living in monotone habitats would have smaller pangenome [76]. Most of the Neisseria species colonize on the mucosa, which may be the reason that the pangenome size is relatively small compared with other niche diversity species [77, 78].…”
Section: Resultsmentioning
confidence: 99%
“…The power law regression analysis of pangenome found that both Neisseria genus and each Neisseria pathogen have open pangenome (Figure 3). Most of the Neisseria species colonize on the mucosa but in various individuals, which may lead to the open pangenome but relatively small size compared with other niche diversity species [77, 78]. Secondly, the number of UGNP, UGNMS, and UGNGS is 319, 78, and 452, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The core and pan genomes of H. pylori were studied by Cao et al. that compared 75 H. pylori genomes and found an open and diverse core genome with 1173 conserved protein families and 673 conserved protein domains in the Helicobacter genus . Proposing that genome regions shared by at least 80% of the H. pylori and absent in non H. pylori may have a function in the adaptability and pathogenicity of H. pylori to the human host, they identified 79 such regions comprising 202,359 bp, among others coding for cag PAI, babB, and sabB .…”
Section: Comparative Genomics and Evolutionmentioning
confidence: 99%
“…The core and pan genomes of HP were studied by Cao et al [3] that compared 75 HP genomes and found an open and diverse core genome with 1,173 conserved protein families and 673 conserved protein domains in the Helicobacter genus.…”
Section: Introductionmentioning
confidence: 99%